Adenosine induced ventricular fibrillation in a structurally normal heart: a case report. (December 2017) - Rajkumar, Christopher; Qureshi, Norman; Ng, Fu; Panoulas, Vasileios; Lim, Phang
Abstract Background Adenosine is the first-line pharmacotherapy for termination of supraventricular tachycardia through its action on the atrioventricular node. However, pro-arrhythmic effects of adenosine are also recognised, most notably in the presence of pre-excited atrial fibrillation. In this case report, we describe the induction of ventricular fibrillation in a patient with no demonstrable accessory pathway, nor any other structural heart disease. This rare, idiosyncratic reaction has never previously been reported and is of relevance given the widespread and routine use of adenosine in clinical practice. Case presentation A 26-year-old woman of Cypriot origin presented to our emergency department with a sudden onset of palpitations and chest discomfort. She was healthy, with no previous medical history and no regular medications. An electrocardiogram demonstrated a narrow complex tachycardia with a rate of 194 beats per minute. Following failure of vagal maneuvers to terminate the tachycardia, the assessing physician administered a single intravenous dose of 6 mg adenosine. Our patient instantaneously developed coarse ventricular fibrillation and circulatory collapse. Cardiopulmonary resuscitation was initiated and our patient was rapidly defibrillated to sinus rhythm with a single 150 J direct current shock. A 900-mg loading dose of intravenous amiodarone was commenced and our patient was managed in the cardiac high dependency unit. No further arrhythmias were identified on continuous cardiac monitoring. On review, her presenting electrocardiogram had demonstrated rapidly conducted atrial fibrillation with no evidence of ventricular pre-excitation. Concordantly, her resting electrocardiogram was not suggestive of any accessory pathway. This was conclusively excluded on invasive electrophysiology study, with negative programmed ventricular stimulation up to three extrastimuli. Extensive laboratory investigations were unremarkable and failed to identify an underlying cause for her episode of atrial fibrillation. Furthermore, cardiac magnetic resonance imaging demonstrated a structurally normal heart, with no edema, fibrosis or infarction as well as normal coronary artery anatomy. Conclusions Adenosine remains a safe and highly efficacious therapy for supraventricular tachycardia. However, this unusual case demonstrates the ability of adenosine to induce circulatory collapse and reminds the clinician that prompt access to resuscitation, defibrillation, and transcutaneous pacing equipment is mandatory with every administration of this drug.